A novel coupled two-dimensional unsaturated asymmetric bistable stochastic resonance system for bearing fault detection. (August 2022) - Zhang, Gang; Zhu, Xingyu; Jiang, Zhongjun
Highlights: A novel coupled stochastic resonance system is proposed to solve the output saturation problem of the conventional. The SPD, MFPT and SNR of the system under the influences of different parameters are derived and analyzed. The system has better bearing fault detection ability in different systems with the parameters optimized by adaptive GA. Abstract: A novel coupled two-dimensional unsaturated asymmetric bistable stochastic resonance (NCTUABSR) method is proposed in this paper, which is formed by coupling a new asymmetric bistable controlled system with a monostable control system, and significantly solves the serious output saturation problem of traditional two-dimensional bistable system. Based on the SPD and MFPT, it is found that with the increase of coupling, the depth and distance of double potential wells in two-dimensional space will decrease, which makes the particles more prone to inter-well transition. Combined with SNR, the performance characteristics of NCTUABSR under the influence of different parameters are deeply analyzed. NCTUABSR is applied to different types of bearings for fault signal detection, and adaptive genetic algorithm is used to optimize the parameters. Compared with different coupling systems, it is found that the detection performance of NCTUABSR has the most advantages, indicating that the system has obvious feasibility in practical engineering applications.